A Semiotic analysis on Kanye West’s Runaway short movie - Adil Billa Bagy; Nia Nafisah (Passage: Journal of English Language and Literature, 2023)
This research aims to analyze the short movie Runaway, directed by a Chicago artist and musician, Kanye West, to find the meaning stored in the sign in the work using Roland Barthes’ (1977) semiotic theory. This theory interprets things like words, images, sounds, gestures, and objects to embrace any system of signs regardless of their nature and limitations. According to Barthes (1977), signs are divided into two types, which are denotative and connotative. Denotative is the most apparent meaning of the symbol while connotative describes a concept that is connected to a word or evoked by an emotion or a cultural value. The study has revealed that there are five significant signs in Runaway, in which Kanye West, who is the main character, runs in a forest, a herd of deer, ballerinas in black costumes, the phoenix, and Ku Klux Klan organization. This finding suggests that analyzing literary work like movies, songs, novels, and other forms of art needs more than just literal meaning. There could be other meanings underlying the printed texts or images, which can reveal the cultural values behind the work.